INSTITUSIONALISASI NILAI-NILAI SUFISTIK DI PONDOK PESANTREN BANJARBARU - Ihromi, Ihda (STIT Ibnu Rusyd Tanah Grogot, 2024)
Research on pesantren (Islamic boarding schools) demonstrates the advantages of pesantren as a subculture that represents Sufi values. Among the Sufi values in pesantren are repentance (taubat), piety (wara'), asceticism (zuhud), poverty (faqr), patience (sabar), trust in God (tawakkal), love (mahabbah), knowledge (makrifah), and contentment (ridha). These values are socially constructed through various institutionalized practices. Therefore, the author aims to explore how these Sufi values are institutionalized in the pesantren of Banjarbaru. The author employs a social constructionist approach as the research method, with a descriptive qualitative research design. Data are collected through interviews, observations, and documentation, with data reduction, data display, and data verification techniques for data analysis. The findings of the study are as follows: 1) The institutionalization of Sufi values includes internalization, externalization, and objectivation simultaneously. In the internalization process, there is typification, habitualization, socialization, and indoctrination in the pesantren regarding Sufi values, both as values and as practices of the Sufi path (tarekat), through the pesantren curriculum based on the books Ihya’ ‘Ulum al-Din, Siraj al-Thalibin, and Kifayah al-Atqiya’, as well as through spiritual practices such as mujahadah, collective dhikr, fasting, bai'at (pledge of allegiance), and khalwat (spiritual retreat). In the externalization process, the Sufi values are expressed as ideologies and positive traditions with various adaptations. Objectivation shows the authority of the mursyid (spiritual guide), consistency in the implementation of sharia, rules, and suluk (spiritual conduct). 2) The Sufi values institutionalized in the pesantren include repentance (taubat) as abandoning sins and mistakes; piety (wara') as discipline and selectivity; asceticism (zuhud) as humility and simplicity; poverty (faqr) as independence and responsibility; patience (sabar) as perseverance and personal integrity; trust in God (tawakkal), love (mahabbah), knowledge (makrifah), and contentment (ridha) as obedience and gratitude. 3) The institutionalization of Sufi values in the pesantren contributes significantly to the strengthening of character and moral development.